Extending ChatGPT with the Rest API and plug-ins. (Live courses (O'Reilly (Firm)), 2023)
You can accomplish a lot with ChatGPT just by typing commands into a website, but ChatGPT also exposes a REST API that makes it possible to embed its intelligence into your apps. Imagine writing tools that translate product manuals to other languages or convert VB.NET code to C#. Or what about putting a ChatGPT frontend on your company's SharePoint documents? The ChatGPT API makes all this possible. ChatGPT plug-ins are bits of code that tell ChatGPT how to use an external resource on the internet. They can direct ChatGPT to access up-to-date information, run computations, or use third-party services and to interact with APIs defined by developers, enhancing ChatGPT's capabilities and allowing it to perform a wide range of actions. Done right, they can help businesses provide exceptional customer experiences, increase sales, automate redundant tasks, enhance brand loyalty, and much more. Plug-ins represent an opportunity to build an "app store" for ChatGPT. Along with the ChatGPT REST API, they're the sweet sauce that infuses modern apps and sites with the wizardry that ChatGPT and large language models seem to be bringing to the forefront of computing today. Join Fixie.ai's Matt Welsh, Nicole Butterfield from O'Reilly and other leading experts in the field to learn more about these plug-ins and get in on the ground floor of this explosive new technology. What you'll learn and how you can apply it Explore current ChatGPT plug-ins and use cases Learn how to incorporate plug-ins into your developer workflow Get hands-on insights with rich interactive demos Understand the basics of REST API development This live course is for you because... You're a machine learning product owner or practitioner or a developer building new applications or products with state-of-the-art AI. You want to learn more about ChatGPT plug-ins and understand how they can enhance the tool's capabilities. Recommended follow-up: Read Natural Language Processing with Transformers, revised edition (book) Read Generative Deep Learning, second edition (book) Read Hands-On Generative AI with Transformers and Diffusion Models (book) Read "Serving" (chapter 8 in Reliable Machine Learning) (book) Follow ChatGPT (expert playlist) Read What Are ChatGPT and Its Friends? (report) Read RESTful Web API Patterns and Practices Cookbook (book) Read Mastering API Architecture (book) Read Developing Apps with GPT-4 and ChatGPT (early release book) Please note that slides or supplemental materials are not available for download from this recording. Resources are only provided at the time of the live event.